Three facets of lecturers' support and relations with students' self-efficacy and performance regarding presentations - Schickel, Marco; Schürmann, Linda; Ringeisen, Tobias (Frontiers in Education, 2025)
The present study aimed to investigate how students' presentation self-efficacy and presentation performance are associated with perceived lecturer support within a four-month university course that applied seven specific design principles to promote presentation competence. One hundred fifty-eight students participated in the presentation course. The students reported their self-efficacy regarding presentation skills at the beginning and the end of the course and rated their lecturers' support behaviors — particularly providing good course materials, explaining clearly, and giving feedback — halfway through the course. Presentation performance was assessed after course completion through a practical presentation exam rated by independent raters. We applied established and validated measures to assess self-efficacy, lecturer support, and presentation performance. The study followed a quasi-experimental one-group pretest-posttest field design. Latent change score modeling revealed a significant increase in students' presentation self-efficacy over the course. This increase was positively associated with lecturer support through good course materials and feedback but negatively associated with clear explanations. Among the three support behaviors, only feedback also predicted better performance in the final presentation exam. Findings suggest that adequate course materials and lecturers' feedback are significant factors that foster students' presentation self-efficacy. The inhibitory effect of explaining clearly may relate to difficulties for students in performing complex presentation behaviors during training, leading to a discrepancy between explanation and practice, and thus increasing awareness of their own competence gaps. Overall, the findings highlight the significance of courses designed according to specific principles and complemented by targeted lecturer support in enhancing students' presentation self-efficacy and performance.